The importance of nursing records for health care from the perspective of nurse auditors (Research, Society and Development, 2020)
The nursing record is fundamental in view of the quality of care provided to the patient, it is through the nursing notes and records that the nurse auditor is able to identify the main flaws in the systematization of care. This study aimed to highlight and emphasize the importance of nurses, identifying factors that corroborate process failures due to poorly prepared records in medical records and their dimensions in the audit. This is a descriptive, exploratory study with a qualitative approach, carried out through a systematic literature review. For this purpose, articles in national journals were searched in the databases SCIELO, LILACS, BIREME and BVS, published between the years 2009 and the first semester of 2019. After the full reading of all manuscripts framed in the inclusion criteria, the sample final consisted of 8 complete scientific texts. The study identified the following flaws in nursing notes and records: spelling errors, erasures, use of non-standard acronyms, incorrect terminology, medication checks and procedures not performed. It was concluded that the record in the patient's medical record of the assistance provided covers several aspects and supports ethically and legally the professional responsible for the care, as well as qualifies the assistance to the patient. When this record is scarce and inadequate, it compromises the care provided to the patient, as well as the institution and the nursing team.